2018
DOI: 10.1111/febs.14518
|View full text |Cite
|
Sign up to set email alerts
|

Early activation of CD95 is limited and localized to the cytotoxic synapse

Abstract: The cytotoxic synapse formed between cytotoxic T lymphocytes or natural killer cells expressing CD95L and target cells with CD95 on their surface is a key pathway for apoptosis induction by the immune system. Despite similarities with the immune synapse in antigen presenting cells, little is known about the role of the spatiotemporal organization of agonistic proteins/receptor interactions for CD95 signaling. Here, we have developed an artificial cytotoxic synapse to examine how mobility and geometry of an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Nano-and microlithographic approaches have provided cell-compatible scaffolds to investigate confined ligand-receptor interactions (Manz & Groves, 2010;Nair et al, 2011;Torres et al, 2008). Various techniques, ranging from photolithography to polymer lift-off and microcontact printing (µCP), have yielded information on how topology and mobility of the stimulus regulate cell responses (Bernard et al, 2000;Doh & Irvine, 2006;Mossman et al, 2005;Sánchez et al, 2018;Traub et al, 2016). So far, these methods utilize receptor ligands or antibodies to induce a rather static cluster formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-and microlithographic approaches have provided cell-compatible scaffolds to investigate confined ligand-receptor interactions (Manz & Groves, 2010;Nair et al, 2011;Torres et al, 2008). Various techniques, ranging from photolithography to polymer lift-off and microcontact printing (µCP), have yielded information on how topology and mobility of the stimulus regulate cell responses (Bernard et al, 2000;Doh & Irvine, 2006;Mossman et al, 2005;Sánchez et al, 2018;Traub et al, 2016). So far, these methods utilize receptor ligands or antibodies to induce a rather static cluster formation.…”
Section: Introductionmentioning
confidence: 99%
“…Nano- and microlithographic approaches have provided cell-compatible scaffolds to investigate confined ligand-receptor interactions. Various techniques, ranging from photolithography (Chen et al ., 2021; Scheideler et al ., 2020; Traub et al ., 2016) to electron-beam lithography (Cai et al ., 2018; Nassereddine et al ., 2021) and microcontact printing (μCP) (Lindner et al ., 2018; Sánchez et al ., 2018), have yielded information on how topology and mobility of the stimulus regulate cellular outcomes. Recently, optogenetics and optochemistry have provided the possibility of targeting receptor oligomerization with high spatiotemporal control (Bardhan & Deiters, 2019; Goglia & Toettcher, 2019; Taslimi et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nano- and microlithographic approaches have provided cell-compatible scaffolds to investigate confined ligand–receptor interactions. Various techniques, ranging from photolithography to electron-beam lithography , and microcontact printing (μCP), , have yielded information on how topology and mobility of the stimulus regulate cellular outcomes. One of the main drawbacks of these systems is that the cells are in contact with the functionalized matrices for minutes/hours before the response is evaluated, thus missing the early signaling events upon cluster formation.…”
mentioning
confidence: 99%
“…It could be shown that secretion of two to four cytotoxic granula of NK cells could lead to the induction of target cell death [125]. Both mechanisms, are taking place at the immunological synapse [126,127]. Further, NK cells are known to be serial killer.…”
Section: Natural Killer Cells As Cellular Immunotherapymentioning
confidence: 99%